Manejo Sostenible de la ganadería en Latinoamérica: Revisión Sistemática 2018-2021. - Silva Ruiz, Lucy (2022)
The livestock system is considered one of the most polluting activities, due to the deforestation that is carried out to expand the pasture coverage, causing ecological imbalances such as soil degradation, air pollution, low CO2 storage, gas emissions greenhouse effect, caused by enteric fermentation of cattle. Although it is true that it is an activity that many families benefit from, however, the lack of public policies aimed at this activity makes it develop in an unsustainable way, damaging the balance of ecosystem services in the long term. The aim of this article is to carry out a systematic review of the conceptual premises of sustainable livestock management in Latin America, for which the PRISMA methodology was used, reviewing the repositories of EBSCO, ProQuest, Scielo and Scopus from the years 2018 to 2021, having as conclusions that the application of sustainable livestock management, in the majority seeks an orientation more towards the care of the ecosystem.